Modernity to Resistance: Marxism and Extension - Gupto , Arun (State, Society and Development: PMPD Perspectives, 2026)
Marxism and left intellectualism are experiencing decline across South Asia, partly because left ideas have historically been communicated without aesthetic sensitivity, and because a gap persists between Marxism as party politics and Marxism as academic methodology. This paper revisits and reinscribes ideas first explored in the author’s earlier booklet, Healing Thoughts on Tender Theory and Discourses on Literature and Culture, reconsidering them through decades of intervening scholarly development. The paper traces how Marxist and leftist concerns extend beyond classical political economy into modernity critique, historiography, visual art, and postcolonial pedagogy, while examining Marxism’s specific trajectory within Nepali higher education. Employing a qualitative, interpretive design grounded in close textual and visual analysis, the study draws on philosophical sources (Kant, Nietzsche, Habermas, Marx, Horkheimer, and Adorno) alongside a nineteenth three twentieth-century paintings, read through deconstructionist, feminist, and postcolonial frameworks. The analysis reveals that Enlightenment rationality, despite its progressive aspirations, functioned as a Eurocentric grand narrative that marginalized non-European and subaltern experience. Marxist historiography, alongside New Historicist and cultural materialist approaches, offers a corrective by relocating history within contested, ideologically situated storytelling. Visual artists independently registered this critique, giving aesthetic form to the failures of Enlightenment progress. The paper argues that Marxism’s academic and methodological value—particularly in shaping subaltern studies, postcolonial theory, and gender-inclusive pedagogy at Nepali universities—persists independently of its declining political fortunes, offering a model for sustaining critical humanities education amid shifting political landscapes.